2017
DOI: 10.1002/cctc.201701302
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Assisted Selective Oxidation of 5‐Hydroxymethylfurfural in Water under Mild Conditions

Abstract: What was the biggest surprise?It would be the controllable selectivity to 5-formyl-2-furoic acid (FFCA) and2 ,5-furandicarboxylic acid (FDCA). Selectivity to the desired product is alwaysaproblem in the oxidation of 5-hydroxymethylfurfural (HMF), not only because HMF is easily converted to other chemicals, but also because there are several intermediate stages duringt he sequential oxidationp rocess. However,o wing to the different reactionr ates of each intermediate, we found that we are ablet oc ontrol the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…As a matter of fact, both HPLC and ESI-mass analysis showed the presence of other compounds, within which we saw the presence of maleic acid. This compound has already been found in literature as a derivative of HMF oxidation [ 79 ] using H 2 O 2 [ 80 , 81 ]; so it is possible that hydrogen peroxide formed by radical reaction using TiO 2 as the photocatalyst in water [ 69 ] promoted the formation of this compound. Other by-products might be formed in reactions with reactive oxygen species produced by the photocatalytic reaction over TiO 2 (such as h+, • O 2 − , • OH, and H 2 O 2 ); in fact, it is well known that aliphatic intermediates can be obtained from molecules that are able to form a peroxy-bridge, as also observed in the photooxidation of phenol [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a matter of fact, both HPLC and ESI-mass analysis showed the presence of other compounds, within which we saw the presence of maleic acid. This compound has already been found in literature as a derivative of HMF oxidation [ 79 ] using H 2 O 2 [ 80 , 81 ]; so it is possible that hydrogen peroxide formed by radical reaction using TiO 2 as the photocatalyst in water [ 69 ] promoted the formation of this compound. Other by-products might be formed in reactions with reactive oxygen species produced by the photocatalytic reaction over TiO 2 (such as h+, • O 2 − , • OH, and H 2 O 2 ); in fact, it is well known that aliphatic intermediates can be obtained from molecules that are able to form a peroxy-bridge, as also observed in the photooxidation of phenol [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to maximum product separation capability, oxidation of HMF is considered as advantageous process to produce FDCA in an economical way [27]. Various catalytic systems involving heterogeneous catalysts [28], homogeneous catalysts [29], and bio-catalysts [30] have been reported for this process in aqueous media as well as organic and biphasic systems [31]. Eectrochemical [32] and photocatalytic [33] processes have also been studied for HMF oxidation to FDCA.…”
Section: Methodsmentioning
confidence: 99%
“…However, the need of high O 2 pressure in the oxidation of HMF to FDCA raises safety issues. Therefore, H 2 O 2 which produces O 2 and water was tested in place of O 2 in the oxidation of HMF to FDCA (Chen C. T. et al, 2018). Chen C. T. et al (2018) reported a high yield of 91% FDCA when a molar ratio of 10 between HMF and Ru/C was used in Na 2 CO 3 solution at 75 • C and a reaction time of 6 h with H 2 O 2 as the oxidant.…”
Section: H 2 O 2 As An Oxidantmentioning
confidence: 99%